Diversidade e padrões de uso do espaço de anfíbios anuros da área de proteção ambiental do Ibirapuitã - Bolzan, Ana Maria Rigon (2014)
Studies of biodiversity surveys and habitat requirements are essential in landscapes threatened by anthropogenic conversion, such as those that make up the Pampa biome. In the present study we determined the spatial distribution of richness of anurans at the Área de Proteção Ambiental (APA) do Ibirapuitã, the largest protected federal area within the Pampa biome in Brazil. Thus we: (1) describe the composition of anuran community regarding species richness, abundance, constancy of occurrence and reproductive modes; (2) compare the frogs composition with other localities of grassland southernmost of South America; (3) tested whether local variables of waterbodies, space and landscape are determinants of species richness, and (4) tested whether environmental heterogeneity influences the structure of anuran community. Sampling was carried from October to November 2012 and at November 2013, the searching at breeding sites method, tadpole collecting and examination of specimens housed in herpetological collections. A total of 64 waterbodies (40 ponds and 24 streams) were sampled for the anuran amphibians, as well as were recorded environmental descriptors in three scales: local, space, and landscape. We recorded the occurrence of 33 anuran species at the APA Ibirapuitã. The registered anurans are typical of open areas, and at least 10% of them are restricted of the grassland areas to the subtropical region of South America, including two endangered species at the global and state levels. Pseudopaludicola falcipes was the most abundant species and Hypsiboas pulchellus was the species most frequently recorded. Five reproductive modes were recorded, and the deposition and the development of exotrophic tadpoles in lentic waterbodies was the most common mode (57.5%). Cluster analysis revealed five groups with more than 50% similarity, whose structure was influenced by geographic distance, but can be partially interpreted by regional peculiarities. We used generalized regression models considering the set of descriptors as predictors of anuran species richness. Subsequently, we use a partition of variance to evaluate the independent and shared explicability between different sets of predictors. Finally, we use a Canonical Redundancy Analysis to explore the role of environmental descriptors on the species abundance of frogs in ponds and streams. The richness in ponds was influenced by the local variable representing the area of waterbodies. Already the abundance was correlated with the percentage of vegetation on the shores and the water temperature. In streams, the species richness of anurans was correlated with a local variable (number of strata of emergent vegetation) and a landscape variable (distance in relation to human residences). Species abundance was affected by higher vegetation strata (> 200 cm) on the shores and by water electrical conductivity. The combined contribution of local and landscape variables have important implications for understanding how amphibians are distributed in the grassland environment. Our work shows the importance of conserving grassland biomes which are increasingly threatened by human activities.